2017
DOI: 10.2147/oaem.s133074
|View full text |Cite
|
Sign up to set email alerts
|

Is a mechanical-assist device better than manual chest compression? A randomized controlled trial

Abstract: BackgroundChest compression quality is a determinant of survival from sudden cardiac arrest. The CPR RsQ Assist Device (CPR RAD) is a new cardiopulmonary resuscitation device for chest compression. It is operated manually but it does not pull up on the chest on the up stroke. The aim of this study was to compare the CPR RAD with standard manual compression in terms of chest compression quality in a manikin model.MethodsParticipants were randomly assigned to either the device or manual chest compression group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…According to a study by Yuksen et al ., there was no difference between the depth of the CPR compressions obtained in a stable setting by MCCD and that obtained by a health-care professional. [ 10 ] Similar to our study, Fox et al . found that paramedics performed the appropriate chest compression depth by 67%.…”
Section: Discussionsupporting
confidence: 91%
“…According to a study by Yuksen et al ., there was no difference between the depth of the CPR compressions obtained in a stable setting by MCCD and that obtained by a health-care professional. [ 10 ] Similar to our study, Fox et al . found that paramedics performed the appropriate chest compression depth by 67%.…”
Section: Discussionsupporting
confidence: 91%
“…According to a study by Yuksen et al, there was no difference between the depth of the CPR compressions obtained in a stable setting by MCCD and that obtained by a healthcare professional. 10 Similar to our study, Fox et al found that paramedics performed the appropriate chest compression depth by 67%. 11 In two different studies, the compression application difference between EMS professionals and two different automated-CPR devices was evaluated, and the compression depth provided by automated-CPR devices was found to be more appropriate than those of paramedics.…”
Section: Discussionsupporting
confidence: 90%
“…[ 3 , 30 31 32 33 34 35 , 74 ] Real-time AVF is one strategy identified by the AHA and ILCOR as a strategy that may improve guideline adherence and IHCA outcomes. [ 27 33 35 ] Simulated studies show improved CPR quality with feedback devices [Tables 2 and 3 ];[ 42 44 45 ], 48 ,, 52 ,[ 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 ] however, the evidence for improvement in clinical outcomes is still very limited [Tables 4 and 5 ]. [ 3 51 73 74 ] That said, these devices have also been shown to be easy to use by both medical professionals and lay persons[ 45 ] and remain an understudied opportunity to improve IHCA outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Stand-alone AVF devices provide benefits in cost and simplicity, making them potentially useful for applications both in-and outside of hospital settings. Despite an abundance of non-randomized and simulation studies [Tables 2 and 3 42 44 45 48 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 ] data from clinical randomized controlled trials (RCT) are sparse [ Table 4 ]. [ 3 51 73 74 ] To date, there have been no < 15 non-AED compression AVF devices have been released to market [ Table 1 ].…”
Section: Introductionmentioning
confidence: 99%